APPLICATION OF COMPUTER TECHNOLOGY IN DISTANCE LEARNING - Shushakova, A.S.; Alimbaeva, A.S. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The article analyzes the results of the implemention of distance technology into the educational process, aimed at the realization of learning activities. Particular attention is paid to the description of the unique possibilities of distance learning technology, the use of which creates the preconditions for the intensification of educational activities.
Keywords: distance learning; form; technology; ways